The systematic use of the Decree-law to allocate extraordinary credits. About the Constitutional Court’s judgment nº126/2016, 7th July - Gómez Lugo, Yolanda (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
Annually, the Government has been using the budgetary technique of extraordinary credits to comply with obligations under the so-called “Special Armament Programs” of the Ministry of Defence. Thus, during 2012, 2103, 2104 and 2015 Government issued provisional normative provisions through Decree-law in order to allocate these budgetary credits, in lieu of introducing bills for its parliamentary processing and approval. Last July 7th, the Spanish Constitutional Court issued a ruling considering the question of whether the use of the Decree-law for allocating extraordinary credits is in accordance with the Constitution. In this paper, through a critical comment of this ruling, I examine the constitutional issues raised by the use of the Decree-law in order to modify the current Budget through the approval of extraordinary credits. Specifically, this issue will be analyzed in the light of the Decree-law 10/2014 and the Constitutional Court’s judgment nº126/2016 holding that the systematic use of emergency legislation to allocate extraordinary credits is unconstitutional. doi: http://dx.doi.org/10.20318/eunomia.2016.3281